(untitled) (Research, Society and Development, 2024)
Introduction: Berger’s disease is a nephropathy characterized by the deposition of IgA in the renal mesangium, which can progress to chronic renal failure, a fact that justifies the relevance of its clinical approach. Objectives: This study aims to review contemporary and multidisciplinary approaches to the diagnosis and treatment of IgA nephropathy, also known as Berger’s disease, highlighting recent advances and scientific gaps. Materials and Methods: This is an integrative literature review on the general clinical characteristics of IgA-induced nephropathy. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Berger’s disease”; “IgA nephropathy”; “Propaedeutics” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: The articles analysed showed that the pathophysiology of Berger’s disease is characterized by the aberrant action of the immune system, which favours the deposition of IgA in the kidneys. The clinical picture is varied and stems from the immune-mediated inflammatory process. The diagnosis of IgA nephropathy is confirmed by renal biopsy, which detects immunocomplexes under microscopy. Conclusion: Berger’s disease is an immune-mediated disease with a complex pathophysiology and a variable clinical picture, which can be mild or severe. Diagnosis is based on a combination of clinical data and complementary tests, and treatment includes various pharmacological measures.